THE IMPLEMENTATION OF READY-MADE GRAPHIC ORGANIZERS ENHANCING STUDENTS’ READING COMPREHENSION ABILITY - Anita Luisa Manoppo; Livianni Lambe (SoCul: International Journal of Research in Social Cultural Issues, 2025)
Reading is a fundamental language skill that enables individuals to acquire knowledge and improve their opportunities in life. Without strong reading abilities, people may struggle academically and professionally. However, many learners encounter difficulties when reading texts, especially those written in a non-native language. To overcome these challenges, educators need to apply effective teaching strategies and tools. This study focused on improving students’ ability to comprehend procedural texts at SMP Negeri 5 Manado by using ready-to-use graphic organizers. The research involved ninth-grade students divided into two groups: a treatment group of 27 students who used graphic organizers, and a control group of 26 students who were taught through traditional lecturing methods. The graphic organizers were designed to help students understand and remember the structure of procedural texts, including goals, materials or tools, and steps or instructions. A quasi-experimental design was used, with participants assigned through a lottery system. The study was conducted over eight sessions, and students’ performance was measured using pre-tests and post-tests focusing on content and language aspects. Data analysis using the Mann-Whitney U test showed significant differences between the two groups. The treatment group achieved a higher average score of 38.85 compared to 14.72 in the control group. These findings indicate that students who used graphic organizers demonstrated better comprehension of procedural text structures. Overall, the study concludes that the use of tailored graphic organizers is an effective strategy for improving students’ reading skills.